1999
DOI: 10.1042/bj3420231
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Janus kinase (JAK)/signal transducters and activators of transcription (STAT) cascade in advanced glycation end-product-induced cellular mitogenesis in NRK-49F cells

Abstract: Advanced glycation end product (AGE) is important in the pathogenesis of diabetic nephropathy, which is characterized by cellular hypertrophy/hyperplasia leading to renal fibrosis. However, the signal transduction pathways of AGE remain poorly understood. The Janus kinase (JAK)/signal transducers and activators of transcription (STAT) pathway has been associated with cellular proliferation in some extra-renal cells. Because interstitial fibroblast proliferation might be important in renal fibrosis, we studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Briefly, a 30 mg sample of cell lysate was subjected to electrophoresis on 12% sodium dodecyl sulfate-polyacrylamide gels. 39 The samples were then electroblotted on polyvinylidene difluoride membranes. After blocking, blots were incubated with antibody in blocking solution for 1 h followed by two 5-min washes in phosphatebuffered saline containing 0.1% Tween 20.…”
Section: Immunoblottingmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, a 30 mg sample of cell lysate was subjected to electrophoresis on 12% sodium dodecyl sulfate-polyacrylamide gels. 39 The samples were then electroblotted on polyvinylidene difluoride membranes. After blocking, blots were incubated with antibody in blocking solution for 1 h followed by two 5-min washes in phosphatebuffered saline containing 0.1% Tween 20.…”
Section: Immunoblottingmentioning
confidence: 99%
“…Briefly, 8 Â 10 6 cells were harvested and suspended in hypotonic buffer A (10 mM HEPES, pH 7.6, 10 mM KCl, 1 mM DTT, 0.1 mM EDTA, and 0.5 mM phenylmethylsulfonyl fluoride) for 10 min on ice and vortexed for 10 s. 39 Nuclei were pelleted by centrifugation at 12 000 g for 5 min. The supernatants containing cytosolic proteins were collected.…”
Section: Preparation Of Nuclear Extractsmentioning
confidence: 99%
“…The activated JAK2 tyrosine-phosphorylate and the latent cytoplasmic STAT3 are involved in AGE-induced cell damage (35). In the present study, it was found that the activation of JAK2 and STAT3 were associated with the AGEs.…”
Section: Discussionmentioning
confidence: 99%
“…Using the UUO model, we then found that, during the fibrotic process, patchy promotion of tubular epithelial proliferation and survival, and interstitial cell apoptosis were linked spatially and temporally with increased pERK expression (12). There is evidence of an interactive mechanistic pathway between the MAPK signalling pathway and JAK/STAT signalling (18,19), and for a role for the JAK/ STAT pathway in kidney fibrosis (3)(4)(5)(6). In this study, where we investigated mRNA for JAK1, JAK2 and JAK3, only JAK3 mRNA had any marked change using the established in vitro model with cells central to development of fibrosis (tubular epithelium and renal fibroblasts).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the JAK/STAT signalling pathway may mediate signalling initiated by reactive oxygen species, as well as other pro-fibrotic factors such as cytokines, growth factors and angiotensin II (3,4). Renal fibroblast (NRK49F) proliferation induced by advanced glycation endproducts (AGE), often formed after oxidative stress, occurred through a JAK/STAT-dependent pathway (3,5,6), but only in association with JAK2 activation and not any of the other members of the JAK family (JAK1, JAK3 or TYK2). Koike et al (4) reported that JAK/STAT activation had a protective role against kidney fibrosis in the unilateral ureteral obstruction (UUO) model of kidney fibrosis in mice; but, Pang et al (7) found that use of a STAT3 inhibitor attenuated kidney tubulointerstitial fibrosis in the same rodent model.…”
Section: Introductionmentioning
confidence: 99%